Identifikasi Penyakit Kulit dan Pemeriksaan Lesi Kulit kepada Masyarakat di Daerah Binaan Universitas Andalas - Qaira Anum; Rina Gustia; Satya Wydya Yenny; Gardenia Akhyar; Ennesta Asri; Tutty Ariani; Mutia Sari; Rizkia Chairani Asri (Warta Pengabdian Andalas, 2021)
Universitas Andalas has an assisted area in the campus environment located in Limau Manis, Pauh. Skin disease, commonly encountered in the community, is a critical disease group in primary healthcare. However, there is no data on skin disease prevalence in Pauh Primary Care Unit. The purpose of this community service is to find out the characteristics of skin diseases that exist in the Pauh Primary Care Unit. Identifying the prevalence of skin disease is indispensable to planning health services and providing preventive actions against related diseases. The method used primary data from dermatologic status examinations on September 14, 2021. In addition, patients' quality of life was assessed using the Dermatology Life Quality Index (DLQI) questionnaire. The activity results obtained the most diseases were superficial fungal infections, and most skin diseases impact the patient's life. So, treatment and education are essential things in this activity.